Translational control of the human erythropoietin expression via an upstream open reading frame in cardiac tissue - Ferrão, José (2017)
Cellular stress activates an integrated stress response, which includes rapid changes in global and gene-specific translation. Translational regulation of specific transcripts mostly occurs at mRNA translation initiation and is mediated via different cis-acting elements present in the mRNA 5’ untranslated region (5’UTR), such as upstream open reading frames (uORFs). uORFs modulate translation of the main ORF by decreasing the number and/or efficiency of scanning ribosomes to reinitiate at the start codon of the main ORF. Human erythropoietin (EPO) is a glycoprotein synthesized and released mainly from the kidney, which has a key role in hematopoiesis. However, recent studies have revealed that EPO is a multifunctional molecule produced and utilized by many tissues that rapidly responds to different cell stress stimuli and tissue injuries. The 5’UTR sequence of the human EPO mRNA has one uORF with 14 codons, which is conserved among different species, indicating its potential role in translational regulation. To test whether EPO expression is translationally regulated in response to ischemia in cardiac tissue, reporter constructs containing the normal or mutant EPO 5’UTR fused to the Firefly luciferase cistron were expressed in H9c2 (heart myoblasts) and C2C12 (muscle myoblasts) cell lines. Luminometry assays revealed that the EPO uORF represses translation of the main ORF in both cell lines. Under chemical ischemia, EPO uORF-mediated translation repression is specifically released in muscle cells. In response to chemical hypoxia, translational derepression occurs in both cell lines. We are currently exploring additional mechanisms through which EPO cardioprotection effects are regulated at the translational level.